2018
DOI: 10.1007/s00018-018-2968-8
|View full text |Cite
|
Sign up to set email alerts
|

Structural disorder in the proteome and interactome of Alkhurma virus (ALKV)

Abstract: Infection by the Alkhurma virus (ALKV) leading to the Alkhurma hemorrhagic fever is a common thread in Saudi Arabia, with no efficient treatment or prevention available as of yet. Although the rational drug design traditionally uses information on known 3D structures of viral proteins, intrinsically disordered proteins (i.e., functional proteins that do not possess unique 3D structures), with their multitude of disorder-dependent functions, are crucial for the biology of viruses. Here, viruses utilize disorder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 173 publications
(238 reference statements)
1
16
0
Order By: Relevance
“…In general, viruses, due to their limited protein-coding capacity, could gain several functional advantages from IDPs/IDPRs in terms of assembly of replication complexes involving a large number of viral and host proteins and survival in extreme host environments [12]. In recent studies, we have shown the prevalence of IDPs/IDPRs and their functional significance in Zika virus (ZIKV) and Chikungunya virus (CHIKV) [13,14], as well as in Hepatitis C virus (HCV) [15], human immunodeficiency virus-1 (HIV-1) [16], various human papillomaviruses (HPVs) [17], respiratory syncytial virus (RSV) [18], Dengue virus [19], MERS-CoV [20], and Alkhurma virus (ALKV) [21].…”
Section: Introductionmentioning
confidence: 99%
“…In general, viruses, due to their limited protein-coding capacity, could gain several functional advantages from IDPs/IDPRs in terms of assembly of replication complexes involving a large number of viral and host proteins and survival in extreme host environments [12]. In recent studies, we have shown the prevalence of IDPs/IDPRs and their functional significance in Zika virus (ZIKV) and Chikungunya virus (CHIKV) [13,14], as well as in Hepatitis C virus (HCV) [15], human immunodeficiency virus-1 (HIV-1) [16], various human papillomaviruses (HPVs) [17], respiratory syncytial virus (RSV) [18], Dengue virus [19], MERS-CoV [20], and Alkhurma virus (ALKV) [21].…”
Section: Introductionmentioning
confidence: 99%
“…The penetrance of disorder in the proteins from flaviviruses and ZIKV has already been analyzed [23,24,25]. The abundance and specific functionality of intrinsically disordered proteins in viral proteomes in general have been considered in several large-scale computational studies [26,27] and have been specifically analyzed for human papillomaviruses [28,29], different strains of the influenza virus [30], human immunodeficiency virus type -1 (HIV-1) [31], human hepatitis C virus [32,33], Dengue virus [34], respiratory syncytial virus [35], Chikungunya virus [36], and Alkhurma virus [37]. Furthermore, previous studies have found correlations between virulence and the shell disorder of DENV and flaviviruses, although the sets used in those studies did not include ZIKV proteins [2,14].…”
Section: Introductionmentioning
confidence: 99%
“…(2019) reported IDRs rich in MoRFs in several structural and non‐structural proteins of human T‐lymphotropic virus type‐1, including those involved in virus replication and genomic RNA binding. Similar results on the role of IDRs present in the viral proteomes have been reported for zika virus (Giri et al ., 2016; Mishra, Uversky, & Giri, 2018), chikungunya virus (Singh et al ., 2018), HPVs (Uversky et al ., 2006), dengue virus (Meng et al ., 2015), respiratory syncytial virus (Whelan et al ., 2016) and alkhurma virus (Redwan, Aljaddawi, & Uversky, 2019). Cook et al .…”
Section: Intrinsic Disorder In Proteinsmentioning
confidence: 99%